PERAN ORGANIZATIONAL COMMITMENT PADA KARYAWAN GENERASI MILENIAL PERHOTELAN - Alfina Juhriyah; Andreas Wahyu Gunawan Putra (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
The low level of innovative behavior and organizational commitment among millennial employees in the hospitality sector poses a serious challenge to organizational sustainability in the digital era. This study aims to analyze the influence of job crafting and perceived organizational support on innovative behavior with organizational commitment as a mediating variable among hotel employees in Central Jakarta. Using a quantitative approach, data were collected through an online questionnaire from 200 respondents selected using a purposive sampling technique. Data analysis was performed using descriptive statistics with the help of SPSS version 26 and Structural Equation Modeling (SEM) through AMOS version 24 software. The results showed that job crafting and perceived organizational support had a positive and significant effect on organizational commitment and innovative behavior. In addition, organizational commitment was proven to significantly mediate the influence of both independent variables on employee innovative behavior partially. In conclusion, hospitality management needs to create a supportive work environment and provide space for employees to make work adjustments to increase emotional engagement that will ultimately trigger the emergence of innovative ideas on an ongoing basis to maintain the organization's competitive advantage.